Electronic screen buffer film and preparation method thereof

By adjusting the composition and structure of the silicon gel layer, combining the antistatic coating and fluorin release film, the poor bonding, insufficient waterproofness and electrostatic adsorption of the electronic screen protector in the prior art are solved, and high Electronic screen buffer film with strength, good viscosity and stable antistatic properties.

CN119119902APending Publication Date: 2024-12-13HUBEI XIANGYUAN NEW MATERIAL TECH INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411371192.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When facing complex mobile phone structures, existing electronic screen protectors cannot completely fill gaps, have poor bonding, insufficient waterproofness, and unstable antistatic properties, resulting in reduced viscosity and electrostatic adsorption problems.

Method used

Using an electronic screen buffer film composed of methyl MQ resin, silicone polymer, epoxy silicone and other materials, the proportion of crosslinking agent and structural control agent is adjusted to increase the antistatic agent and tackifier to form a high A silicon gel layer with strength, good viscosity and antistatic properties, and an antistatic coating and a fluorin release film are provided on the surface.

Benefits of technology

The initial fracture performance and ductility of the silicon gel layer are improved, the gap filling capacity and adhesion are enhanced, the electrostatic adsorption is reduced, the stable surface resistance and better impact absorption performance are achieved, and the process flow is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119902A_ABST
    Figure CN119119902A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electronic screen protection materials, and particularly relates to an electronic screen buffer film and a preparation method thereof. The electronic screen buffer film is prepared from the following components in parts by mass: 12 to 24 parts of methyl MQ resin, 64.5 to 76.5 parts of a siloxane polymer, 0.7 to 1 part of a catalyst, 0.1 to 0.5 part of an inhibitor, 1.8 to 3 parts of a first tackifier, 0.3 to 1.5 parts of an antistatic agent and 3.6 to 6 parts of a second tackifier, the first tackifier is one or more of epoxy siloxane, acryloyloxy siloxane or methacryloyloxy alkane; the second tackifier is one or more of epoxy siloxane, acryloyloxy siloxane and methacryloyloxy alkane; the second tackifier is one or more of rosin resin, petroleum resin or terpene resin. The tackifier is added into the silica gel buffer material, the reaction crosslinking degree is adjusted, the problem that a conventional adhesive tape or a gel product is insufficient in viscosity is solved, and the mechanical performance of the screen protection film is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of electronic screen protection materials, and more specifically, relates to an electronic screen buffer film and a preparation method thereof. Background Art

[0002] With the development of science and technology, the size of smartphone screens is not only getting bigger, but the design and structure of the screens have also changed a lot. Acrylic foam tape has an absolute advantage in screen fixation and is the preferred solution for mobile phone screen fixation. However, the current complex mobile phone structure makes the existing foam unable to meet the requirements. In addition, acrylic foam tape cannot meet 100% gap filling in the face of complex structures, and there are many processing steps.

[0003] New technologies and requirements such as LED, ultra-thin, waterproof, 5G, wireless charging, and wifi charging are driving a huge change in mobile phones. Now, glass back covers and ceramic back covers, mobile phone screens have been widely adopted and vigorously developed with the advent of new technologies. However, due to the complex processing technology of glass and ceramics themselves and the characteristics of these materials themselves, mobile phone design has brought great challenges. Currently, acrylic foam tape is widely used in the market, but how to overcome manufacturing tolerances and achieve perfect bonding, shock absorption, and waterproofing functions can no longer be fully met by conventional tapes. At the same time, foam tapes need to be coated or glued twice after foam molding, and the process path is cumbersome.

[0004] With the development of science and technology, the size of smartphone screens is not only getting bigger, but the design and structure of the screens have also changed a lot. Acrylic foam tape has an absolute advantage in screen fixation and is the preferred solution for mobile phone screen fixation. However, the current complex mobile phone structure makes the existing foam unable to meet the requirements. In addition, acrylic foam tape cannot meet 100% gap filling in the face of complex structures, and there are many processing steps.

[0005] Patent document CN114316896A discloses silicone gel, preparation method and protective film using the silicone gel; by adjusting the number of side hydrogens of hydrogen-containing silicone oil, the density of the network structure is regulated, and at the same time, the introduction of single-end hydrogen-containing silicone oil can make the structure have side chain units, which can be used for stress buffering and improve the impact resistance of silicone gel. At the same time, the document proposes that due to the presence of free methyl MQ resin, a certain steric hindrance effect is produced, resulting in a decrease in the degree of crosslinking, which reduces the density of the three-dimensional network structure. Even when there is no methyl MQ resin, the performance of the protective film is better. However, in actual use, since it does not have a certain peeling and bonding effect, the overall viscosity of the silicone gel is very low or even non-existent, and it is easy to overflow during the cutting and attachment of the silicone gel, and the assembly is not convenient enough; the peeling and bonding effect of the silicone gel is insufficient, and the bonding effect under the screen is poor during actual use, and there will be deviations with use; at the same time, its impact absorption performance needs to be further improved.

[0006] Moreover, most of the existing silicone gel protective films lack anti-static adsorption effects and are prone to adsorb dust during use; even if a single internal or external anti-static method is used, a good anti-static channel cannot be formed and the anti-static value cannot be stabilized. Summary of the invention

[0007] In view of the defects of the prior art, the present application provides an electronic screen buffer film, which includes, based on 100 parts by mass, 12 to 24 parts of methyl MQ resin, 64.5 to 76.5 parts of siloxane polymer, 0.7 to 1 part of catalyst, 0.1 to 0.5 parts of inhibitor, 1.8 to 3 parts of first tackifier, 0.3 to 1.5 parts of antistatic agent and 3.6 to 6 parts of second tackifier;

[0008] The first tackifier is one or more of epoxysiloxane, acryloxysiloxane or methacryloxyethane; the second tackifier is one or more of rosin resin, petroleum resin or terpene resin.

[0009] Preferably, the siloxane polymer is cross-linked and polymerized by 61 to 72 parts of vinyl siloxane, 1.2 to 3.5 parts of a cross-linking agent, and 1.5 to 3 parts of a structure control agent.

[0010] As further preferred, the crosslinking agent and the structure control agent are each independently hydrogen-containing polysiloxane.

[0011] More preferably, the hydrogen content of the hydrogen-containing polysiloxane used as the cross-linking agent is 1.0 wt% to 1.6 wt% and the viscosity is 23.0 to 35.0 mPa·s.

[0012] More preferably, the hydrogen content of the hydrogen-containing polysiloxane as the structure control agent is 0.05 wt% to 0.08 wt% and the viscosity is 20 to 60 mPa·s.

[0013] As further preferred, the antistatic agent is carbon nanotubes.

[0014] As further preferred, the carbon nanotubes are single-walled carbon nanotubes with a tube diameter of 1 nm to 2 nm and an electrical conductivity greater than 150EC (s / cm).

[0015] Preferably, an antistatic coating of 0.1 μm to 1 μm is provided on the surface of one side of the electronic screen buffer film.

[0016] As further preferred, the antistatic coating comprises sodium alkyl sulfonate.

[0017] As further preferred, a fluorine release film is also provided on the surface of the electronic screen buffer film at a side away from the antistatic coating.

[0018] As further preferred, a substrate is further provided on a side of the antistatic coating away from the electronic screen buffer film.

[0019] As further preferred, the material of the substrate is PET (polyethylene terephthalate).

[0020] Preferably, the thickness of the electronic screen buffer film is 55 μm to 180 μm.

[0021] Preferably, the methyl MQ resin has an M / Q ratio of 0.5 to 1.2, a molecular weight of 2000 to 7000, a hydroxyl content of less than 0.3%, and a viscosity of 6000 cp to 7000 cp.

[0022] The present application also provides a method for preparing the above-mentioned electronic screen buffer film, comprising: coating a solution of raw materials for the electronic screen buffer film on a substrate and vulcanizing and drying the solution, wherein the raw materials include, based on a total of 100 parts by mass, 12 to 24 parts of methyl MQ resin, 61 to 72 parts of vinyl siloxane, 1.2 to 3.5 parts of a cross-linking agent, 1.5 to 3 parts of a structure control agent, 0.7 to 1 part of a catalyst, 0.1 to 0.5 parts of an inhibitor, 1.8 to 3 parts of a first thickener, 0.3 to 1.5 parts of an antistatic agent, and 3.6 to 6 parts of a second thickener; the mass of the solvent in the solution of the raw materials is 30% to 60% of the mass of the raw materials, and the solvent is one or more of ethyl acetate or xylene.

[0023] Preferably, before coating the solution of the raw material of the electronic screen buffer film on the substrate, the method further comprises coating 0.3wt% to 2wt% of sodium alkyl sulfonate solution on the substrate and drying.

[0024] As further preferred, the solvent of the sodium alkyl sulfonate solution is polyethylene glycol, ethanol or water.

[0025] In general, compared with the prior art, the above technical scheme conceived by the present application firstly improves the initial fracture performance of the entire silicone gel buffer film by adjusting the amount of the cross-linking agent and adding the structure control agent, and has good ductility, which can fully play the gap-filling role and have high strength at the same time; by adding a variety of tackifiers to the formula of the silicone gel buffer film, the overall viscosity of the overall silicone gel after curing and molding is improved, ensuring that the electronic screen buffer material has better impact absorption and cutting properties in a thinner case, and has high-strength self-adhesion, perfectly adheres to different electronic screen components, and reduces the risk of degumming and overflow contamination; at the same time, it is preferred to add antistatic agents and antistatic coatings to give the final product a better and more stable surface resistance. The technical solution of the present application can solve this problem, resulting in the process of die-cutting and attachment, which is not easy to be contaminated by environmental dust and eliminates the influence of static electricity; specifically, the present application has the following advantages:

[0026] 1. The present invention enhances the mechanical properties of the screen protective film by adding the first tackifier and the second tackifier to the electronic screen buffer film, and overcomes the problem that the peeling force of the substrate tape protective film is attenuated and the viscosity is reduced under high temperature and high humidity; it has been verified that the embodiment of the present invention is tested using the GB / T 25256-2010 optical functional film 180° peeling force and residual adhesion rate test method. The initial peeling force of the steel plate tested at room temperature is greater than 1600g / in, and the peeling force after double 85 aging is greater than 1400g / in; the surface resistance is <10 when tested by a volume resistivity meter. 7 Ω / sq, density is 1000kg / m 3 ~1300kg / m 3 , the elongation at break of buffer silicone gel is ≥400%; due to the improvement of peeling force and tensile strength, the strength of the electronic screen buffer film is improved, solving the problem of entanglement after attachment and cutting;

[0027] 2. Due to the characteristics of silicone gel itself, it is easy to absorb dust during use, resulting in defects; however, this application adds antistatic agents in the formula and the manufacturing process, and the antistatic agent transferability on the surface of the film material can meet the antistatic performance, which can avoid the absorption of dust and affect the screen performance;

[0028] 3. The present application has better impact absorption performance than the prior art. It has been verified that through the test of a 10g ball and a drop distance of 55mm, the impact absorption rate of the electronic screen buffer film of 110μm to 180μm is greater than 20%, and the impact absorption rate of the electronic screen buffer film of 55μm to 110μm is greater than 10%;

[0029] 4. This application adopts one-time molding to reduce the complexity of the process, and at the same time has better waterproof properties than conventional tape screen protectors. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic diagram of the preparation method of an embodiment of the present application; from bottom to top are a fluorine release film, a 55μm to 180μm silicone gel layer, an electrostatic coating, and a PET substrate. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0032] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the feature. In the description of the present application, "plurality" means two or more, unless otherwise clearly and specifically defined.

[0033] In addition, references throughout this specification to "one embodiment"; "one embodiment", "an example" or similar language indicate that a particular feature, structure, or characteristic described in conjunction with the embodiment is included in at least one embodiment of the present application. Thus, appearances of the phrase "in one embodiment"; "in one embodiment" and similar language throughout this specification may, but do not necessarily, all refer to the same embodiment.

[0034] To achieve the above object, the present application provides an electronic screen buffer film, which comprises, from bottom to top: a fluorine release film, a silicone gel layer and a PET substrate as a substrate, such as Figure 1 As shown; there is an antistatic coating with a thickness of 0.1μm to 1μm between the PET substrate and the silicone gel layer, and the antistatic coating is sodium alkyl sulfonate; the thickness of the silicone gel layer is 50μm to 180μm, the fluorine release film is a light release film with a release force of 1g to 5g; the thickness of the PET substrate is about 36μm to 100μm. Among them, the fluorine release film and the PET substrate will be peeled off during use, and only the silicone gel layer and the antistatic coating play a buffering and protective role for the electronic screen.

[0035] The components of the silicone gel layer as the main body of the electronic screen buffer film include, based on 100 parts by mass, 12 to 24 parts of methyl MQ resin, 64.5 to 76.5 parts of siloxane polymer, 0.7 to 1 part of catalyst, 0.1 to 0.5 parts of inhibitor, 1.8 to 3 parts of first tackifier, 0.3 to 1.5 parts of antistatic agent and 3.6 to 6 parts of second tackifier;

[0036] The first tackifier is one or more of epoxysiloxane, acryloxysiloxane or methacryloxyethane; the second tackifier is one or more of rosin resin, petroleum resin or terpene resin.

[0037] In some embodiments, the siloxane polymer is cross-linked and polymerized by 61 to 72 parts of vinyl siloxane, 1.2 to 3.5 parts of a cross-linking agent, and 1.5 to 3 parts of a structure control agent; in other embodiments, the cross-linking agent and the structure control agent are each independently a hydrogen-containing polysiloxane with different hydrogen contents.

[0038] The methyl MQ resin has an M / Q ratio of 0.5 to 1.2, a molecular weight of 2000 to 7000, a hydroxyl content of <0.3%, a viscosity of 6000 to 7000 cp, preferably an M / Q ratio of 0.6 to 0.9, and a commercially available finished product with a solid content of 60% ± 5% can be used; the vinyl siloxane has a viscosity of 60000 to 100000, a vinyl content of 0.02wt% to 0.06wt%, a viscosity of 5000 to 80000, preferably a vinyl content of 0.024wt% to 0.06wt%, and is used for Provide SI-C=C bond to participate in the cross-linking reaction; the cross-linking agent is a hydrogen-containing polysiloxane with a hydrogen content of 1.0wt% to 1.6wt% and a viscosity of 23.0mpa·s to 35.0mpa·s; used to provide SI-H bond to participate in the reaction, the hydrogen content affects the cross-linking degree, impact absorption and peeling force; the structure control agent is a hydrogen-containing polysiloxane with a hydrogen content of 0.05wt% to 0.08wt% and a viscosity of 20mpa·s to 60mpa·s, providing a lower content of side SI-H bond to affect the elongation at break; the first viscosity increasing agent The first tackifier is one or more of epoxy siloxane, acryloxy siloxane or methacryloyloxy siloxane, which can provide multifunctional groups, increase the degree of branching, improve the cohesion of silicone gel, and affect the peeling force; the second tackifier is rosin resin or petroleum resin, terpene resin, which provides higher adhesion performance and initial viscosity, and affects the peeling force and self-strength; if only the second tackifier is added, the cohesion of the silicone gel after molding is relatively poor, and the first tackifier needs to be added to the formula to ensure the increase of viscosity and increase the cohesion effect of itself, and it is not easy to produce residual glue during vulcanization, which is relatively The peel force attenuation after aging is reduced, and the tensile properties are improved to a certain extent. The more suitable mixing ratio is 1: (1.2-3), and the more preferred ratio is 1: 2; the catalyst is preferably a Custer Perkin catalyst, PT-3000 or PT-4000, and the platinum content is 2000ppm to 10000ppm; in one embodiment, 1-ethynyl-1-cyclohexanol is used as an inhibitor to inhibit the effectiveness of the catalyst at room temperature and inhibit the reaction from occurring. During the mixing, stirring and coating process of the rubber, no cross-linking reaction occurs in the rubber, thereby extending the service life and processing time of the rubber.

[0039] In some embodiments, carbon nanotubes can be selected as antistatic agents. The carbon nanotubes can be single-walled carbon nanotubes or multi-walled carbon nanotubes, preferably single-walled carbon nanotubes. The carbon nanotubes have a diameter of 1 nm to 2 nm and a conductivity of >150EC (s / cm).

[0040] Another object of the present application is to provide a method for preparing an electronic screen buffer material, comprising: coating an antistatic coating, preparing a silicone gel layer, and covering a fluorine release film on the surface of the silicone gel layer;

[0041] The coating of the antistatic coating comprises coating the antistatic coating on a substrate of a PET substrate of 36 μm to 100 μm, drying and rolling up the substrate after being placed in an oven at 50° C. to 80° C. for 30 seconds to 90 seconds; the electrostatic coating liquid is a 0.3wt% to 2wt% sodium alkyl sulfonate solution, and the solvent of the sodium alkyl sulfonate solution is polyethylene glycol, ethanol or water;

[0042] Wherein, preparing the silicone gel layer comprises coating a solution of raw materials of the electronic screen buffer film on a substrate on the surface of the PET substrate on which the antistatic coating is formed and vulcanizing and drying, wherein the raw materials comprise, by weight, 12 to 24 parts of methyl MQ resin, 61 to 72 parts of vinyl siloxane, 1.2 to 3.5 parts of a cross-linking agent, 1.5 to 3 parts of a structure control agent, 0.7 to 1 part of a catalyst, 0.1 to 0.5 parts of an inhibitor, 1.8 to 3 parts of a first tackifier, 0.3 to 1.5 parts of an antistatic agent, and 3.6 to 6 parts of a second tackifier; the mass of the solvent in the solution is 30% to 60% of the mass of the raw material, and the solvent is one or more of ethyl acetate or xylene; after vulcanization and drying (the vulcanization conditions can use a vulcanization procedure of 50-80-150-100-50°C), the thickness of the silicone gel layer of the main body is about 55 μm to 180 μm;

[0043] Finally, a fluorine release film is applied to the side of the silicone gel layer away from the PET substrate and rolled into a finished product.

[0044] In actual use, the PET substrate will be peeled off first, and the antistatic coating will be transferred to the silicone gel surface during peeling. Then the side with the antistatic coating will be attached to the electronic screen. The antistatic coating can further prevent the adsorption of dust, making the attachment smoother. Finally, the fluorine release film will be torn off to complete the use of the electronic screen buffer material.

[0045] The following contents are examples

[0046] Example 1

[0047] raw material:

[0048] Methyl MQ resin: molecular weight 6000, M / Q ratio 0.6-0.9, viscosity 6000-7000cp, solid content 60% Hubei Longsheng Sihai New Materials;

[0049] Vinyl siloxane: viscosity 65000cSt, vinyl content 0.03mmol / g, Ambiah specialty silicone;

[0050] Crosslinking agent: 1.6% hydrogenated silicone oil, viscosity 24 cSt , Runhe Silicone;

[0051] Structure control agent: hydrogenated silicone oil, hydrogen content 0.05%, Ambiah special silicone;

[0052] The first adhesion promoter: 3-methacryloxypropyltrimethoxysilane, Shin-Etsu Co., Ltd., Japan;

[0053] Second tackifier: esterified rosin resin, Zhejiang Xinsong resin;

[0054] Catalyst: Custer platinum catalyst, 3000ppm, Shaanxi Ruike New Materials;

[0055] Inhibitor: 1-ethynyl-1-cyclohexanol, Guangzhou Siyou New Materials;

[0056] Antistatic agent: single-walled carbon nanotubes, Beijing Dekedaojin Technology.

[0057] 1. Raw material preparation

[0058] 1.1 Prepare electrostatic coating solution

[0059] Sodium alkyl sulfonate was added to ethanol to dilute the solution into an electrostatic coating liquid having a sodium alkyl sulfonate content of 1.6 wt%.

[0060] 1.2 Prepare the rubber

[0061] Mix 20g of methyl MQ resin, 65g of vinyl siloxane, 2.4g of a cross-linking agent (hydrogen-containing silicone oil with a hydrogen content of 1.6%), 2g of a structure control agent (hydrogen-containing silicone oil with a hydrogen content of 0.05%), 2.4g of a first tackifier, 4.8g of a second tackifier, 1g of a catalyst, 0.4g of an inhibitor and 2g of an antistatic agent, and add 35g of ethyl acetate (Wuhan Xiangheyi Chemical) for dilution to form a rubber compound.

[0062] 2. Preparation of electronic screen buffer materials

[0063] 2.1 Adding antistatic agent to PET substrate

[0064] The electrostatic coating liquid prepared in step 1.1 was coated on the PET substrate, passed through an oven at 80°C, and dried after 90s to obtain an antistatic layer of 1 μm.

[0065] 2.2 Preparation of silicone gel layer

[0066] The rubber material was coated on one side of the PET substrate with the antistatic layer by a coating doctor blade method, and vulcanized for 3 minutes in a 5-section temperature-controlled drying oven at 50-80-150-150-80°C. After drying, a silicone gel layer of 110 μm was obtained.

[0067] 2.3 Cover the silicone gel layer with a fluorine release film and roll it up into a finished product

[0068] 3. Use

[0069] After the above steps, the electronic screen buffer material has been produced. Figure 1 As shown in the figure, from top to bottom, it includes a PET substrate, a silicone gel layer and a fluorine release film, and the antistatic layer is located on the side of the silicone gel layer close to the PET substrate. In actual use, the film of the PET substrate is torn off to expose the side of the silicone gel layer covered with the antistatic layer and fit it to the electronic screen, and then the fluorine release film is removed to complete it.

[0070] Example 2-Example 5, Comparative Example 1-Comparative Example 5

[0071] The same steps are repeated in Example 2 to Example 5 and Comparative Example 1 to Comparative Example 5, except that the masses of the components in step 1.2 are adjusted according to Table 1, and the mass units are all g; wherein, step 2.1 is omitted in Comparative Example 5, and the rubber is directly coated on a PET substrate without an antistatic layer; the thicknesses of the other examples and comparative examples are also roughly the same as that of Example 1.

[0072] Table 1 Component mass of Example 2-Example 5, Comparative Example 1-Comparative Example 5

[0073]

[0074]

[0075] Embodiment 6-7

[0076] The same steps as in Example 1 were repeated, except that in step 2.2, a scraper was used to control the thickness of the coated rubber. After drying, the thickness of the silicone gel layer in Example 6 and Example 7 was 55 μm and 180 μm, respectively.

[0077] Example 8

[0078] Example 1 was repeated with the same steps, except that, in step 1.2, 60 g of xylene was used instead of 35 g of ethyl acetate.

[0079] Example 9

[0080] Example 1 was repeated with the same steps, except that in step 1.1, the electrostatic coating liquid prepared consisted of a 2 wt % solution of sodium alkyl sulfonate in water.

[0081] Example 10

[0082] Example 1 was repeated with the same steps, except that in step 1.1, the electrostatic coating liquid prepared consisted of a 0.3 wt % solution of sodium alkyl sulfonate in polyethylene glycol.

[0083] Experimental results verification

[0084] Verification Example 1: Impact Absorption Test

[0085] Cut the silicone gel samples of the examples and comparative examples into 5 cm × 10 cm. Place them on the stress sensing device platform at the bottom of the impact absorption device under standard laboratory environment. Use a 10g iron ball to drop freely from a height of 55mm, read the maximum stress before and after placing the sample, and measure its impact absorption rate, where:

[0086] Impact absorption rate = (maximum stress value before placing the sample - maximum stress value after placing the sample) / maximum stress value before placing the silicone gel × 100%.

[0087] The measurement results are shown in Table 2.

[0088] Verification Example 2 Peel Force Test

[0089] The embodiments and comparative examples were tested using the national standard GB / T 25256-2010 optical functional film, release film 180° peel force and residual adhesion rate test method. Under room temperature conditions, the test results of the initial and aged peel force are shown in Table 2.

[0090] Verification Example 3: Surface resistance test

[0091] Take the embodiment and comparative example samples of appropriate size, tear off the PET antistatic film, and test the side originally in contact with the PET antistatic film using an ASTM-D-257 volume resistivity meter. Take three different points for the test, take the average value after reading, and the results are shown in Table 2.

[0092] Verification Example 4 Density Test

[0093] The density of the silicone gel parts of the embodiment and the comparative example was tested using a density balance. The results are shown in Table 2.

[0094] Verification Example 5 Elongation at break

[0095] According to the ASTM D3759 standard of the American Society for Materials, a tensile test was performed on the embodiments and comparative examples using a universal tensile testing machine. The results are shown in Table 2.

[0096] Table 2 Experimental results of the embodiments and comparative examples

[0097]

[0098]

[0099] It can be seen from the experimental results that in the actual effect of the present application, the impact absorption rate is related to the thickness. Generally, the thicker the thickness, the greater the impact absorption rate. The impact absorption rate of the embodiment is greater than 10% when the thickness is 55μm-110μm; compared with the comparative example, the impact absorption rate of the embodiment with the same thickness can be stably greater than 20% when the thickness is 110μm-180μm; the increase of MQ resin can improve the impact absorption rate, and it is also affected by the degree of cross-linking of the colloid. The increase in the degree of cross-linking can improve the impact absorption rate to a certain extent.

[0100] The initial peeling force of the steel plate tested at room temperature is stable and greater than 1600g / in, and the peeling force after double 85 aging is also greater than 1400g / in, indicating that the embodiment of the present application has a high peeling force effect, and the high peeling force is related to the added methyl MQ resin and the tackifying resin of the second tackifier. With the increase of methyl MQ resin and tackifying resin, the peeling force gradually increases; however, if the content of the two substances is added blindly, the groups participating in the cross-linking reaction of the main body are reduced, the compatibility is deteriorated, and the cohesion of the finished product is deteriorated, the peeling performance of the finished product is poor, and the peeling force is prone to a significant decrease after aging; optimizing the ratio of the first tackifier and the second tackifier can improve the compatibility of the colloid, improve the cohesion, improve the stability of the peeling force, and ensure that the peeling force attenuation after aging is reduced;

[0101] The elongation at break of the embodiments of the present application is also greater than 400%, and the density is between 1000 and 1300 kg / m 3 , indicating that its physical properties have been improved. The elongation at break and density of the product are related to the degree of crosslinking. Adding more crosslinking agent will easily lead to an increase in the degree of crosslinking of the finished product, a decrease in the elongation at break of the product, and a decrease in the initial peeling force. This application adjusts the amount of crosslinking agent and simultaneously increases the structure control agent to increase the crosslinking fulcrum, ultimately ensuring that the elongation at break of the finished product is greater than 400%, and other properties are also within the range;

[0102] At the same time, the surface resistance is tested to be within 10 7Ω / sq or less, indicating that its antistatic performance has also been improved. Conventionally, it is difficult to form good antistatic properties for thicker products or silicone products. This application adds carbon nanotubes inside through cross-linking to form an internal electron path, and adds an electron channel layer on the outer surface, and finally completes a perfect electrostatic channel through the product, completes the transfer of charge, and thus forms good antistatic properties. This application also compares the method of simply adding carbon nanotubes or antistatic surface attachment. The final effect is not as good as the effect of superimposing the two methods at the same time, and the stability of the antistatic performance is also improved; it has been verified that Examples 8-10 also show properties similar to Examples 1-5, indicating that a small range adjustment of the solution concentration and the replacement of similar solvents have no significant effect on the final product performance, and can be replaced according to practicality or environmental protection.

[0103] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electronic screen buffer film, characterized in that: The total weight parts are 100 parts: 12 to 24 parts of methyl MQ resin, 64.5 to 76.5 parts of siloxane polymer, 0.7 to 1 part of catalyst, 0.1 to 0.5 parts of inhibitor, 1.8 to 3 parts of first tackifier, 0.3 to 1.5 parts of antistatic agent and 3.6 to 6 parts of second tackifier; The first tackifier is one or more of epoxysiloxane, acryloxysiloxane or methacryloxyethane; the second tackifier is one or more of rosin resin, petroleum resin or terpene resin.

2. The electronic screen buffer film according to claim 1, characterized in that: The siloxane polymer is cross-linked and polymerized by 61 to 72 parts of vinyl siloxane, 1.2 to 3.5 parts of a cross-linking agent and 1.5 to 3 parts of a structure control agent.

3. The electronic screen buffer film according to claim 2, characterized in that: The crosslinking agent and the structure control agent are each independently hydrogen-containing polysiloxane; the hydrogen content of the hydrogen-containing polysiloxane as the crosslinking agent is 1.0 wt % to 1.6 wt %, and the hydrogen content of the hydrogen-containing polysiloxane as the structure control agent is 0.05 wt % to 0.08 wt %.

4. The electronic screen buffer film according to claim 1, characterized in that: The antistatic agent is carbon nanotube.

5. The electronic screen buffer film according to claim 1, characterized in that: A 0.1 μm to 1 μm antistatic coating is arranged on the surface of one side of the electronic screen buffer film.

6. The electronic screen buffer film according to claim 1, characterized in that: The component of the antistatic coating is sodium alkyl sulfonate.

7. The electronic screen buffer film according to claim 1, characterized in that: The thickness of the electronic screen buffer film is 55 μm to 180 μm.

8. The method for preparing the electronic screen buffer film according to any one of claims 1 to 7, characterized in that: A solution of raw materials for an electronic screen buffer film is coated on a substrate and vulcanized and dried. The raw materials include, based on a total of 100 parts by mass, 12 to 24 parts of methyl MQ resin, 61 to 72 parts of vinyl siloxane, 1.2 to 3.5 parts of a cross-linking agent, 1.5 to 3 parts of a structure control agent, 0.7 to 1 part of a catalyst, 0.1 to 0.5 parts of an inhibitor, 1.8 to 3 parts of a first tackifier, 0.3 to 1.5 parts of an antistatic agent, and 3.6 to 6 parts of a second tackifier; the mass of the solvent in the solution of the raw materials is 30% to 60% of the mass of the raw materials, and the solvent is one or more of ethyl acetate or xylene.

9. The preparation method according to claim 8, characterized in that: Before coating the solution of the raw material of the electronic screen buffer film on the substrate, the method also includes coating 0.3wt%-2wt% of sodium alkyl sulfonate solution on the substrate and drying it.

10. The preparation method according to claim 9, characterized in that: The solvent of the sodium alkyl sulfonate solution is polyethylene glycol, ethanol or water.